Nephrotic Syndrome . Anatomo- clinical evaluation of corticosteroid treatment - Olivo Vargas, Rómulo (1965)
In contrast to the concept that on Nefrósico Syndrome be had in the past, when a degenerative disease túbulis was accepted, is now considered ( 1, 7 , 39) that primitive disorder of Nefrósico Syndrome sits mainly in the basal membrane glomerulus , allowing increased permeability , especially for low molecular weight proteins ( Aliaand Gamma- globulins ) and only secondarily then occurs tubular alterations. Nefrósico syndrome , characterized clinically by marked edema, albuminaria , hypoalbuminemia and hypercholesterolemia , is presented in a series of processes , such as some Diffuse glomerulonephritis Chronic Renal amyloidosis , Diabetes Mellitus ( Kimmelstiel -Wilson syndrome ) , thrombosis renal vein , infectious (syphilis and malaria ) , effects of various drugs ( mercurial compounds , etc.).